Legal Liability of Ex-Directors for the Management of the Company During the term of Office Period Has Ended - Pande Putu Indahyani Lestari; I Gede Agus Kurniawan (Dinasti Research, 2024)
This research aims to analyze the legal responsibility of former Directors for the management of the Company which was carried out when the term of office of the Directors and Board of Commissioners had ended before the re-appointment GMS was held. In this case, the Board of Directors is the organ of the Company which is fully responsible for the management of the Company and represents the Company both inside and outside the Court. Directors whose term of office ends do not automatically continue their position as before, except by re-appointment based on a GMS decision. So that the management carried out after the term of office ends may conflict with the law and the Company's articles of association. The approaches used are the statutory approach and the case approach. The results of legal actions carried out by former Directors while continuing to manage and represent the Company are illegal actions and can be held personally responsible. However, if it can be proven that the management actions are carried out in good faith for the sake of the law and provide good benefits for the Company and all of the Company's stakeholders, then based on the authority possessed by UUPT and the Company's articles of association, the GMS can decide to make all legal actions in the form of management. What is done by the former Director becomes a legal act and the Company's responsibility, so that the former Director is free from personal responsibility.